Acute toxicity of Pistacia atlantica green seeds on Sprague- Dawley rat model - Dyary, Hiewa Othman; Rahman, Heshu Sulaiman; Othman, Hemn Hassan; Mohammad, Snur; Abdullah, Rasedee (Sulaimani Journal for Pure and Applied Sciences, 2017)
The acute toxic effect of the aqueous extract of Pistacia atlantica green seeds was investigated in groups of Sprague-Dawley rats at oral doses of 200, 400, and 800 mg/kg body weight. After 14 days, there was no significant difference (p>0.05) in behavior, food and water consumption, body weight gain, and hematological and serum biochemical parameters between untreated control and extract-treated rats. There were lesions in the liver and kidney indicating that aqueous P. atlantica seed extract causes some hepatoxicity and nephrotoxicity in rats.
Keywords: Pistacia atlantica; Acute toxicity; Animal model; Mount Atlas mastic tree